DEVELOPING AN INCLUSIVE SERVICESCAPE FOR THE ELDERLY, PERSONS WITH DISABILITIES, AND PREGNANT WOMEN: A CASE STUDY OF MINASA BAJI VILLAGE OFFICE, MAROS DISTRICT - Irman, Arif Aprilia Jaya Ganda; Salsadila, Nurazizah; Esmati, Shahabuddin (Politeknik STIA LAN Makassar, 2025)
Public service delivery in Indonesia often overlooks the specific needs of vulnerable groups, such as elderly citizens, persons with disabilities, and pregnant women. Despite policy commitments to inclusivity, such as those outlined in Law No. 25 of 2009 on Public Services, implementation at the village level remains limited, revealing a gap between regulatory intent and service practice. This study examines how inclusive service design can bridge that gap through the creation of a dedicated “services cape” at the Minasa Baji Village Office, Maros Regency. Anchored in the framework of inclusive public administration, the study explores how physical space and participatory planning contribute to equitable service access. Using a qualitative approach involving interviews, observation, and documentation, data were collected from village officials and representatives of vulnerable groups to co-develop a specialized service room. The initiative, trialed for 11 days with minimal funding, yielding preliminary insights that would guide future improvements. This change project successfully improved public service quality by reducing average waiting time by over 66%, increasing accessibility by 100%, achieving near-perfect information clarity, enhancing visitor satisfaction, and improving operational cost efficiency, with an overall success rate of 87.2%. The findings demonstrate that low-cost, community-driven innovations can effectively enhance inclusivity and service efficiency. Theoretically, this study advances the discourse on inclusive governance by highlighting the role of participatory spatial design in promoting equitable access within grassroots public administration contexts.